1976
DOI: 10.1128/iai.14.2.555-563.1976
|View full text |Cite
|
Sign up to set email alerts
|

Lysis and killing of bacteria by lysosomal proteinases

Abstract: The bacteriolytic and bactericidal effects of the human proteinases cathepsin B, cathepsin D, cathepsin G, and elastase were investigated. Cathepsin G and elastase were 5 to 10% as active as egg white lysozyme in the lysis of Micrococcus lysodeikticus. All four enzymes slowly lysed the lysozyme-resistant Staphylococcus aureus. The gram-negative Acinetobacter 199A was rendered sensitive to lysozyme by all of the proteinases. Only elastase caused marked proteolysis of the outer membrane, which would permit acces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

1982
1982
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(33 citation statements)
references
References 31 publications
1
31
0
1
Order By: Relevance
“…Of interest, the augmented killing is not compromised by heat‐inactivating HNE enzymatic activity, suggesting that elastolytic action is not a prerequisite for synergy. The independence of anti‐microbial action from enzymatic activity has been observed in studies of PMN– Borrelia interactions (72) and applies to other serprocidins, including cathepsin G (33, 73). Given the cationic nature common to this group of granule proteins, it is reasonable to speculate that their strong electrostatic interactions with the microbial surface disrupt the integrity of the organism, rendering potential targets more accessible to attack.…”
Section: Cooperation Among Anti‐microbial Agents Within the Pmnmentioning
confidence: 91%
See 1 more Smart Citation
“…Of interest, the augmented killing is not compromised by heat‐inactivating HNE enzymatic activity, suggesting that elastolytic action is not a prerequisite for synergy. The independence of anti‐microbial action from enzymatic activity has been observed in studies of PMN– Borrelia interactions (72) and applies to other serprocidins, including cathepsin G (33, 73). Given the cationic nature common to this group of granule proteins, it is reasonable to speculate that their strong electrostatic interactions with the microbial surface disrupt the integrity of the organism, rendering potential targets more accessible to attack.…”
Section: Cooperation Among Anti‐microbial Agents Within the Pmnmentioning
confidence: 91%
“…Additional proteins have been isolated from the cytosolic complex [e.g. p40 phox (29–35)] or shown in broken cell systems to modulate activity [e.g. MRP8/14 (36–38)], indicating that all the regulatory elements of this important system and their specific function remain to be completely identified.…”
Section: Immediate Responses Of Pmns To Stimulationmentioning
confidence: 99%
“…These bacteria appeared to be more sensitive to lysis by nonspecific protease activity (proteinase K) than by specific protease activity (trypsin and chymotrypsin). The ability of proteolytic enzymes to lyse bacteria has been the topic of very few reports (2,11,12,25). Kaur et al (12) demonstrated that elastase purified from Psettdomotias aerttgitwsa caused lysis of freshly cultured cells of grampositive and gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…It is released from neutrophils and accumulates at sites of inflammation when leukocytes are activated by bacterial infection. NE degrades not only extracellular matrix components such as fibrin, fibronectin, and collagen [6][7][8] but also the bacterial wall [9]. Clinically, NE is used as a sensitive serum marker for inflammation [10].…”
Section: Introductionmentioning
confidence: 99%